2008
DOI: 10.1080/00365520701824951
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-ketoglutarate reduces gastrectomy-evoked loss of calvaria and trabecular bone in female rats

Abstract: Gx resulted in loss of calvarial, trabecular and cortical bone in the rat. AKG counteracted the effect of Gx on calvaria and trabecular bone but not on cortical bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 35 publications
1
47
2
Order By: Relevance
“…Several studies have shown that 2-oxoglutaric acid (2-Ox), the precursor to proline, hydroxyproline, glutamate, arginine and asparagine, has an effect on the growth of both human and animal bones. Dietary supplementation with 2-Ox also counteracted the bone loss observed in gastrectomised, fundectomised and ovariectomised animals, as well as in post-menopausal women ( 5 , 6 , 8 14 ) . 2-Ox affects the synthesis of amino acids and proteins, as well as improving their absorption from the gut ( 15 ) .…”
mentioning
confidence: 88%
“…Several studies have shown that 2-oxoglutaric acid (2-Ox), the precursor to proline, hydroxyproline, glutamate, arginine and asparagine, has an effect on the growth of both human and animal bones. Dietary supplementation with 2-Ox also counteracted the bone loss observed in gastrectomised, fundectomised and ovariectomised animals, as well as in post-menopausal women ( 5 , 6 , 8 14 ) . 2-Ox affects the synthesis of amino acids and proteins, as well as improving their absorption from the gut ( 15 ) .…”
mentioning
confidence: 88%
“…Due to its broad roles in multiple biological processes, AKG has been a subject of interest for researchers in various fields [16]. AKG also influences several age-related processes, including stem cell proliferation [17,18] and osteoporosis [19]. To study its role in mammalian aging, animals received sustained CaAKG treatment starting at 18 months of age and determined its effect on 4 survival, as well as the onset of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between letters mean significant differences with P < 0.05. appears to be even more effective in preserving bone structure and mineralization in GCs induced rather than in gastrectomy-induced osteopenia, since there was no improvement in femoral and tibial BMD and BMC of gastrectomized rats receiving even higher dose of 2-Ox in our previous study. 21 The ability to withstand the mechanical forces acting upon a bone and to resist fractures is related to its geometry, mineralization, and quality of structural components such as shape, microarchitecture of trabecular bone, the turnover, collagen and cells regularly spaced throughout the mineralized matrix. 19,28 There are several possible mechanisms of GIO presented in literature: inhibition of bone formation by suppression of genesis and activity of osteoblasts with accelerated osteocyte and osteoblasts apoptosis as well as acceleration of bone resorption by extension of osteoclasts life span.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for the trabecular bone, the number of osseous lacunae per square millimeter of trabeculae, the total area of osseous lacunae per square millimeter of trabeculae, and the mean cross-sectional area of osseous lacunae were assessed as previously described. 18,21,23 Blood sample collection and analysis Blood samples collection and analysis were carried out as described previously. 15,24 Briefly, blood of not fasted piglets was collected from subclavian vein.…”
Section: Histomorphometrymentioning
confidence: 99%